War and occupation in Iraqi fiction - Masmoudi, Ikram (Edinburgh studies in modern Arabic literature, 2015)
Examines tangible experiences of war and occupation in recent Iraqi fiction. This provides a historical contextualisation of the Iraqi novel before and after the fall of Saddam Hussein's regime. It presents an analytical and critical study of a selected corpus of novels about war and occupation in Iraq.